Efektivitas Rehabilitasi Narkotika terhadap Pelaku Tindak Pidana Narkotika yang Mengulangi Perbuatannya: Studi Kasus di Polresta Bukittinggi, Lembaga Rehabilitasi - Putri Yaldi Olivia (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
This study aims to analyze the effectiveness of narcotics rehabilitation for offenders who reoffend after undergoing rehabilitation, using a case study at the Bukittinggi Police Resort (Polresta Bukittinggi) and rehabilitation institutions. This research is motivated by the continued occurrence of narcotics offenders who relapse into criminal behavior despite having completed medical and social rehabilitation programs as mandated by Law Number 35 of 2009 concerning Narcotics. The research method used is empirical juridical with a qualitative approach through interviews, literature review, and case documentation. Primary data were obtained from investigators at Polresta Bukittinggi and rehabilitation institutions, while secondary data were obtained from laws and regulations as well as relevant literature. The results indicate that the investigation process leading to rehabilitation has been conducted in accordance with applicable procedures through assessment mechanisms by the Integrated Assessment Team (Tim Asesmen Terpadu). However, the effectiveness of rehabilitation in preventing recidivism remains suboptimal, as evidenced by offenders who return to narcotics abuse after completing rehabilitation programs. This suggests that rehabilitation programs require continuous supervision and more comprehensive approaches, including medical, psychological, and social aspects, to minimize the risk of relapse among former narcotics abusers.